Friction factors, convective heat transfer coefficients and the Colburn analogy for industrial sugarcane juices - Astolfi-Filho, Zailer [UNESP]; de Oliveira, Eduardo Basilio; dos Reis Coimbra, Jane Selia; Telis-Romero, Javier [UNESP] (Elsevier B.V. Sa, 2012)
Sugarcane (Saccharum sp.) is a relatively low-cost agricultural resource, produced mainly in tropical and subtropical regions of the planet. One of the most important applications of sugarcane juice is in the production of ethanol biofuel. A correct design of unit operations during the sugarcane juice processing requires an accurate characterization of the flow properties (friction factors, rheological behaviour, thermophysical properties and heat transfer coefficients) of this raw material. In this work, friction factors (f) and Nusselt number (Nu) were determined for sugarcane juice in different steps of its processing (untreated sugarcane juice, clarified sugarcane juice and mixed sugarcane juice). For both laminar and turbulent flows, the empirical models for f fitted well (r(2) >= 0.9) with the experimental values obtained by pressure drop measurements. Also. Nu values calculated by applying the empirical correlation of Hausen (for laminar flow) and that of Sieder-Tate (for turbulent flow) presented good adjustment (r(2) >= 0.9) to the experimentally determined values. Thus, the f and Nu values obtained for turbulent flow were taken to verify the Colburn analogy, which furnished results with small deviations (<= 8.9%) from the expected ideal value. This finding indicates the suitability of such analogy in this case, allowing good estimations of heat transfer coefficients from frictions factors, or vice versa, for sugarcane juices in turbulent flow conditions. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Biofuel; Colburn analogy; Ethanol; Friction factor; Heat transfer; Sugarcane